Conditions d’émergence du projet personnel de l’étudiant au sein de situations d’apprentissage formel - Dominique Lagase-Vandercammen; Jean-Pierre Boutinet (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In the past, numerous studies have been carried out on the student’s personal project. Few of them, however, have examined the emergence of the student’s personal project in a context of formal learning. The present empirical research, referring to socio-cognitive theories of motivation, has applied the method of critical incidents to highlight conditions that facilitate or inhibit the emergence of the student’s personal project. The results shows that formal learning situations in higher education support, albeit under particular conditions, students in expliciting their personal project in terms of autonomy, mastery, relational and situational interest.